Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/2049936119838228
|View full text |Cite
|
Sign up to set email alerts
|

Optimal treatment of HIV-associated neurocognitive disorders: myths and reality. A critical review

Abstract: Background: The aim of this study was to review the clinical data on the effectiveness of the pharmacotherapy of HIV-associated neurocognitive disorders (HANDs). Methods: A literature search of PubMed was performed (from January 1996 to October 2018) using the terms: ‘HIV-associated neurocognitive disorders’, ‘HIV-associated dementia’, ‘mild neurocognitive disorder (MND)’, ‘asymptomatic neurocognitive impairment (ANI)’, ‘adjuvant therapies’, ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 77 publications
0
24
0
Order By: Relevance
“…1 The growing burden of HAND justifies a quintessential global response to address this important mental health challenge among people living with HIV (PLWHIV). 2 Before ART was introduced in 1996, 20-30% of people with advanced HIV infection displayed symptoms of severe HAND 3,4 , with death occurring within 6 months 5 . In the ART era, the prevalence of HAND varies between 19% and 64%, averaging globally at about 50%.…”
Section: Introductionmentioning
confidence: 99%
“…1 The growing burden of HAND justifies a quintessential global response to address this important mental health challenge among people living with HIV (PLWHIV). 2 Before ART was introduced in 1996, 20-30% of people with advanced HIV infection displayed symptoms of severe HAND 3,4 , with death occurring within 6 months 5 . In the ART era, the prevalence of HAND varies between 19% and 64%, averaging globally at about 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Our univariate analysis shows a lower prevalence of BBB alteration among participants treated with integrase inhibitors (INSTI), compared with patients treated with other classes of antiviral drugs (protease inhibitors or non–nucleoside reverse transcriptase inhibitors). Integrase inhibitors (Raltegravir, Elvitegravir, Dolutegravir and Bictegravir) are commonly used as first-line cART regimen, in association with other classes of antivirals, such as two nucleoside reverse transcriptase inhibitors [ 27 ]. Moreover, other elements can influence the therapy response, such as HIV DNA, substance abuse, pharmacogenetics, adherence to antiretrovirals and demographic factors, e.g., age and ethnicity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…HAND still represents an unresolved multifactorial complication of HIV, even in the modern cART (traditional three-drug regimen) era that often achieves the suppression of HIV replication to levels below the limit of detection of currently used assays. Indeed, recent studies have demonstrated that no clinical trials of HAND treatments are efficient beyond the optimal suppression of HIV replication in the CNS [ 11 , 12 ]. Whereas some studies have indicated a reduction in cognitive impairment due to cART, patients with a controlled viral load who discontinue treatment with antiretrovirals have shown an improvement in cognitive functions and a reduction in neuronal damage [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent studies have demonstrated that no clinical trials of HAND treatments are efficient beyond the optimal suppression of HIV replication in the CNS [ 11 , 12 ]. Whereas some studies have indicated a reduction in cognitive impairment due to cART, patients with a controlled viral load who discontinue treatment with antiretrovirals have shown an improvement in cognitive functions and a reduction in neuronal damage [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%